Triterpenes and Acylglycerols from Canarium ovatum - Consolacion Y. Ragasa , Oscar B. Torres, Jessa Mae P. Gutierrez, Hannah Patricia Beatriz C. Kristiansen, and Chien-Chang Shen (Journal of Applied Pharmaceutical Science, 2015)
Chemical investigations of the dichloromethane extracts of the leaves of Canarium ovatum Engl. afforded β-amyrin (1a), α-amyrin (1b), epi-β-amyrin (2a), epi-α-amyrin (2b), epi-lupeol (2c), β-carotene (3) and lutein (4); while the twigs yielded 1a-1b. The dichloromethane extracts of the fruits of C. ovatum yielded triacylglycerols (5); the mesocarp also afforded 1a, 1b, 1,2-dioleylglycerol (6), and monounsaturated and saturated fatty acids; the nutshell also provided 6; and the kernel also yielded monounsaturated and saturated fatty acids. The structures of 1-6 and the fatty acids were identified by comparison of their 1H and/or 13C NMR data with those reported in the literature.
Keywords: Canarium ovatum, Burseraceae, &beta; -amyrin, &alpha; -amyrin, epi-&beta; -amyrin, epi-&alpha; -amyrin, epi-lupeol, &beta; -carotene, lutein, triacylglycerols, 1,2-dioleylglycerol.